FEATURES OF PAIN SYNDROME IN PATIENTS WITH PTERYGOPALATINE GANGLIONITIS - I.A. Kolisnyk; P.I. Tkachenko; A.I. Pankevych; A.M. Hohol (Проблеми екології та медицини)
Relevance of the research. The features of complex anatomical and functional organization of the maxillofacial area, peripheral nervous system, as well as autonomic structures determine a variety of pathogenetic mechanisms of prosopalgia, among which the lesions of the pterygopalatine node are the most common. Despite the presence of a significant variety of clinical manifestations of pterygopalatine ganglionitis, the prevalence and variety of autonomic manifestations in this disease, the main complaint of patients is pain, the characteristics of which are quite different. The aim of our research was to study the nature of pain in patients with pterygopalatine ganglionitis. Material and methods of research. We examined 105 patients with pterygopalatine ganglionitis aged from 30 to 74 years. Patients were examined for the nature of pain and its intensity, the predominant time of onset and duration of pain attacks, the place of primary localization of pain and the area of its spread. A visual analog scale (VAS) was used to assess pain intensity. Based on the intensity of pain and depending on the severity of the disease, all patients were divided into three groups: mild, moderate and severe pterygopalatine ganglionitis. With a mild severity of pterygopalatine ganglionitis, the intensity of pain attacks is 4-5 points, lasting up to 30 minutes and with a frequency of 1-3 times a day with localization within one or two anatomical areas. With moderate severity, the intensity of pain attacks is 5-7 points, lasting from 30 minutes to 1-2 hours and with a frequency of 4-5 times a day with the gradual spread of pain from one area to half of the face. The severe course is characterized by pain attacks of 8-10 points, lasting for 2 hours or more and with a frequency of attacks from 4 to 6-10 per day. In addition, the pain, occurring in one anatomical area, gradually spread to half of the face, radiating to neighboring areas. Thus, analyzing the features of the pain syndrome in patients with pterygopalatine ganglionitis, we can conclude: 1. The intensity of pain, which was determined by VAS, increases depending on the severity of ganglionitis and ranges from 4.3 points in mild to 8.75 in severe ganglionitis. 2. The duration and frequency of pain attacks increase from 30 minutes with a frequency of 1-3 seizures per day in patients with mild pterygopalatine ganglionitis, to 2 or more hours and 4-10 seizures per day in patients with severe ganglionitis. 3. The localization of pain attacks extends from one anatomical area in mild ganglionitis to half of the face with the possibility of irradiation of pain in severe ganglionitis. 4. These clinical symptoms should be used in determining the severity of pterygopalatine ganglionitis and the choice of treatment tactics in the future.